The lifting property for classes of mappings - Janusz J. Charatonik (International Journal of Mathematics and Mathematical Sciences)
The lifting property of continua for classes of mappings is defined. It is shown that the property is preserved under the inverse limit operation. The results, when applied to the class of confluent mappings, exhibit conditions under which the induced mapping between hyperspaces is confluent. This generalizes previous results in this topic.